Acyl-CoA-binding protein drives glioblastoma tumorigenesis by sustaining fatty acid oxidation - Duman, Aset Ceren; Yaqubi, Kaneschka; Hoffmann, Angelika; Açıkgöz, Azer Aylin; Korshunov, Andrey; Bendszus, Martin; Herold-Mende, Christel; Liu, Hai-Kun; Alfonso, Julieta (Cell metabolism, 2019)
Glioblastoma multiforme (GBM) undergoes metabolic reprogramming to meet the high ATP and anabolic demands of the tumor cells. However, the role of fatty acid oxidation (FAO) and its regulators in the GBM context has been largely unknown. Here, we show that the neural stem cell pro-proliferative factor acyl-CoA-binding protein (ACBP, also known as DBI) is highly expressed in GBM, and by binding to acyl-CoAs, it cell-autonomously maintains high proliferation rates, promoting tumor growth and poor survival in several preclinical models. Mechanistic experiments using ACBP-acyl-CoA binding affinity variants and pharmacological FAO modulators suggest that ACBP supports tumor growth by controlling the availability of long-chain fatty acyl-CoAs to mitochondria, promoting FAO in GBM. Thus, our findings uncover a critical link between lipid metabolism and GBM progression established by ACBP and offer a potential therapeutic strategy for an effective anti-proliferative metabolic management of GBM.
Gesehen am 08.04.2022